2014
DOI: 10.1007/s00894-014-2336-z
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on the adsorption of benzodiazepines to vermiculite surfaces

Abstract: Widespread use of pharmaceuticals such as benzodiazepines has been resulting over the last decades in the dissemination of residues of these compounds in the environment, and such fact has been raising increasing concern. The generally low efficiencies of conventional wastewater treatment processes for the removal of this type of pollutants demands for the development of alternative or complementary water and wastewater treatment technologies, among which adsorption processes have been gaining popularity, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The use of vermiculite as an adsorbent has been studied for the removal of Hg(II) (Do Nascimento and Masini, 2014), Cr(III) (Badawy et al, 2010;Sis and Uysal, 2014), Cu(II) (Badawy et al, 2010), Pb(II) (Hongo et al, 2012;Sis and Uysal, 2014), Zn(II) (Sis and Uysal, 2014), Cs (Suzuki et al, 2013), Ag(I) (Sari and Tüzen, 2013), Cr(VI) (Dultz et al, 2012), Cd(II) (Panuccio et al, 2009), mineral and canola oils (Mysore et al, 2005), phthalate (Wen et al, 2013), basic cationic dye (Choi and Cho, 1996), herbicides 2,4-D, diuron, alachlor, metolachlor and triazine (de Rezende et al, 2011), dibenzothiophene (Froehner et al, 2010), benzodiazepine (Carvalho et al, 2014) and cationic surfactant cetylpyridinium chloride (Tarasevich et al, 2013) from aqueous solution. Although there are many works published about the adsorption of metal ions and organic compounds onto vermiculite, only one study has been carried out to determine the dye adsorption properties of vermiculite.…”
Section: Introductionmentioning
confidence: 98%
“…The use of vermiculite as an adsorbent has been studied for the removal of Hg(II) (Do Nascimento and Masini, 2014), Cr(III) (Badawy et al, 2010;Sis and Uysal, 2014), Cu(II) (Badawy et al, 2010), Pb(II) (Hongo et al, 2012;Sis and Uysal, 2014), Zn(II) (Sis and Uysal, 2014), Cs (Suzuki et al, 2013), Ag(I) (Sari and Tüzen, 2013), Cr(VI) (Dultz et al, 2012), Cd(II) (Panuccio et al, 2009), mineral and canola oils (Mysore et al, 2005), phthalate (Wen et al, 2013), basic cationic dye (Choi and Cho, 1996), herbicides 2,4-D, diuron, alachlor, metolachlor and triazine (de Rezende et al, 2011), dibenzothiophene (Froehner et al, 2010), benzodiazepine (Carvalho et al, 2014) and cationic surfactant cetylpyridinium chloride (Tarasevich et al, 2013) from aqueous solution. Although there are many works published about the adsorption of metal ions and organic compounds onto vermiculite, only one study has been carried out to determine the dye adsorption properties of vermiculite.…”
Section: Introductionmentioning
confidence: 98%
“…The interaction energies of these complexes are less negative than those of some investigated systems due to the additional contribution of Mg‧‧‧Cl and Mg‧‧‧N interactions. [8,11] Accordingly, interaction of vermiculite surface with benzylpenicillin is weaker than that with chloramphenicol or benzodiazepines.…”
Section: P1 P2mentioning
confidence: 99%
“…Microscopic perspectives (atomic, molecular levels) to phenomena, and processes taking place can be provided or understood. [8,9] In previous experimental and modeling reports on adsorption of organic compounds, especially for antibiotics in wastewater resources, nature and role of interactions formed on surfaces have not been yet elucidated in detail. Moreover, experimental and theoretical studies on adsorption of antibiotic molecules onto vermiculite surface have not been observed clearly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction energies of P1 and P2 configurations are -55.6 and -54.9 kcal.mol -1 , respectively (cf. Table 2) The deformation energy is a characteristic parameter for evaluating the ability of separating the substrate and the surface from its stable configuration [17]. As tabulated in Table 2, these energy values for TiO 2 surface are larger than that for ENR molecule.…”
Section: Energetic Aspects Of Adsorption Processmentioning
confidence: 99%